IMPLEMENTASI UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH TERHADAP PROSES MASA RESES ANGGOTA DPRD KABUPATEN SUKOHARJO DALAM PENJARINGAN ASPIRASI MASYARAKAT UNTUK MEWUJUDKAN PRINSIP KEDAULATAN RAKYAT - Maharani, Andina Elok Puri; Kusuma, Yudan Randy (Res Publica: Jurnal Hukum Kebijakan Publik, 2017)
This study aims to find out how the implementation of Act Number 23 of 2014 on The Local Government againts the recess period process for the DPRD members of Sukoharjo Regency in capturing public aspiration to actualize the principle of popular sovereignty and how regulations order the recess period of parliament members.This study took a sample from five parliament members of five political parties in the DPRD of Sukoharjo Regency.The kind of research used in this research is a normative-empirical and descriptive legal research.The type of used data is primary data and secondary data. The source of primary data is direct interview with related parties of the research. The sources of secondary data are literature, regulations, journals, articles and materials from the internet and other related sources.Technique of  data collection that be used are field studies which directed to the object of research and literature study to obtain theoretical basis related to the research.Based the result of the research and discussion, concluded that the regulation regarding the recess period of DPRD members in Indonesia have regulated in various acts and regulations such as Act Number 27 of 2009 on Majelis Permusyawaratan Rakyat, Dewan Perwakilan Rakyat, dan Dewan Perwakilan Daerah, Act Number 23 of 2014 on Local Government, and Government Regulation Number 16 of 2010 on the Procedures of the Dewan Perwakilan Rakyat Daerah.Each DPRD members of Sukoharjo Regency have commited the mandate of recess according to Article 108 Section (i) and Article 161 Section (i) Act Number 23 of 2014 on Local Government. According to Article 108 Section (i) and Article 161 Section (i) Act Number 23 of 2014 on Local Government, DPRD members of Sukoharjo Regency have been doing periodic visit or recess to visit their constituents in their electoral region.